English Teaching Strategies at Rural Schools: A Case Study of SMPN 2 Plampang - Safitri, Amelia; Yusra, Kamaluddin; Aziz, Atri Dewi; Arifuddin (Journal of English Education Forum (JEEF), 2025)
This study investigates the strategies in teaching English in rural school, SMPN 2 Plampang. The subjects of this study are the English teachers and the 6 students in SMPN 2 Plampang. Qualitative approach with case study was employed in this research. The instrument that used in this study involved semi-structured interviews, along with classroom observations, the researcher used smartphones to records the interviews in order to gather the data needed, for classroom observation, the researcher use observation sheets and videos of the classroom learning situation. Content analysis was used as the data analysis approach for this study. The result of this study indicates four strategies used by the teachers: 1) Translating words meaning; 2) Corse materials matching students’ level and learning situation; 3) Giving motivation; 4) Applying various teaching strategies. From students’ perspective, translating lessons into local languages can help them understand the lesson. Future research should evaluate the effectiveness of these strategies and explore the impact of rural education policies on English learning.